Pest Identification Guide: Common Blossom Thrips - Jeffrey D. Cluever; Hugh A. Smith (EDIS)
This publication is part of the Pest Identification Guides series, which was created to help growers and crop consultants, private homeowners, Master Gardeners, and the general public identify common arthropod pests and the damage they inflict. Each field guide provides photos of the important life stages and crop damage associated with arthropod pests. The text highlights key general morphology and biology, distribution, and natural enemies. Written by Jeffrey Cluever and Hugh Smith, and published by the UF Department of Entomology and Nematology, July 2016.